2022
DOI: 10.1177/00219096221090639
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Urban Distribution of Child Hawking in Southeast Nigeria

Abstract: This article investigated the intra-urban distribution of child hawking in Enugu Municipality, Nigeria. The study first enumerated child hawkers across three residential areas (core, transition and sub-urban) simultaneously on different weekdays and at different locations (activity-nuclei) in Enugu municipality. A questionnaire was then employed to obtain information from 95 incidentally selected child hawkers, comprising 49, 21 and 25, respectively. Information sourced was their socio-economic characteristics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…In line with this finding, the Ministry of Education in Nigeria notes that, of the 42.1 million children eligible for primary education, only 22.3 million are in school, while the remaining 19.8 million are out of school, taking on one economic activity or the other. Similarly, the observation of secondary school enrolment shows that, of the 33.9 million eligible children, only 6.4 million are in school (Taiwo, 2022).…”
Section: Schooling Statusmentioning
confidence: 98%
“…In line with this finding, the Ministry of Education in Nigeria notes that, of the 42.1 million children eligible for primary education, only 22.3 million are in school, while the remaining 19.8 million are out of school, taking on one economic activity or the other. Similarly, the observation of secondary school enrolment shows that, of the 33.9 million eligible children, only 6.4 million are in school (Taiwo, 2022).…”
Section: Schooling Statusmentioning
confidence: 98%
“…The report emphasised that the state employs various strategies, including utilising the media as a means to counter violent narratives, enhancing conflict-sensitive reporting, restricting access to media platforms, and effectively containing the deployment of such platforms by Boko Haram terrorists, in order to safeguard lives and properties in the North East region of Nigeria. Taiwo et al (2021) investigated the attitude of Southeast State inhabitants regarding the broadcast media coverage of events involving "unknown" gunmen in Southeast Nigeria. The investigation revealed that the activities of unidentified armed individuals in Southeast Nigeria can be attributed to inadequate governance.…”
Section: Introductionmentioning
confidence: 99%